2014
DOI: 10.1111/codi.12601
|View full text |Cite
|
Sign up to set email alerts
|

Standardized technique for single port laparoscopic ileostomy and colostomy

Abstract: Single incision stoma siting proves a ready, robust and reliable technique for diversion ileostomy and colostomy with a minimum of operative trauma for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Shah et al . reported that three patients who underwent laparoscopic loop colostomy had no postoperative pain in the first 24 h . However, SPH is a non‐scarring operation of the abdomen, similar to single‐port laparoscopic colostomy, but postoperative pain was induced because of stoma construction in our study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Shah et al . reported that three patients who underwent laparoscopic loop colostomy had no postoperative pain in the first 24 h . However, SPH is a non‐scarring operation of the abdomen, similar to single‐port laparoscopic colostomy, but postoperative pain was induced because of stoma construction in our study.…”
Section: Discussionmentioning
confidence: 53%
“…We consider the SPH to be a non‐scarring operation of the abdomen, and it is associated with less postoperative pain than a multiport Hartmann's procedure (MPH). Previous reports have concluded that single‐incision laparoscopic colostomy is an effective technique . Nguyen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with the conventional laparoscopic procedure, there is currently no consensus on the superiority of the single-port procedure. Some studies have observed no significant difference between single-port and conventional laparoscopic procedures [11,12], while other studies have shown benefits of the single-port procedure over the conventional procedure [13,14]. Some studies even expressed concern about the difficulty and time consumption of the surgical procedure, which can be taxing on the surgeon [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a defunctioning loop ileostomy is a common colorectal and emergency surgical procedure. Different techniques exist, including a recent description of a single port laparoscopic ileostomy formation . We present a video of a 55‐year‐old man with an impeding obstructing rectal tumour who underwent a trephine defunctioning loop ileostomy prior to long course chemoradiotherapy with a novel method using an Alexis ® wound protector.…”
mentioning
confidence: 99%